Pharmacokinetics of single‐dose rivaroxaban under fed state in obese vs. non‐obese subjects: An open‐label controlled clinical trial (RIVOBESE‐PK) - Majdoleen Alalawneh (13961580) (2024)
The evidence of rivaroxaban's pharmacokinetics in obese compared with non‐obese populations remains inconclusive. We aimed to compare the pharmacokinetic profile of rivaroxaban between obese and non‐obese populations under fed state. Participants who met the study's eligibility criteria were assigned into one of two groups: obese (body mass index ≥35 kg/m2) or non‐obese (body mass index 18.5–24.9 kg/m2). A single dose of rivaroxaban 20 mg was orally administered to each participant. Nine blood samples over 48 h, and multiple urine samples over 18 h were collected and analyzed for rivaroxaban concentration using ultra‐performance liquid chromatography coupled with tandem mass detector. Pharmacokinetic parameters were determined using WinNonlin software. Thirty‐six participants were recruited into the study. No significant changes were observed between obese and non‐obese participants in peak plasma concentration, time to reach peak plasma concentration, area under the plasma concentration–time curve over 48 h or to infinity, elimination rate constant, half‐life, apparent volume of distribution, apparent clearance, and fraction of drug excreted unchanged in urine over 18 h. Rivaroxaban's exposure was similar between the obese and non‐obese subjects, and there were no significant differences in other pharmacokinetic parameters between the two groups. These results suggest that dose adjustment for rivaroxaban is probably unwarranted in the obese population. Other Information Published in: Clinical and Translational Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/cts.13853